Medial Calcar Comminution and Intramedullary Nail Failure in Unstable Geriatric Trochanteric Hip Fractures - Seth M. Tarrant; David Graan; Drew J. Tarrant; Raymond G. Kim; Zsolt J. Balogh (Medicina, 2021)
Background and Objectives: An increasing global burden of geriatric hip fractures is anticipated. The appropriate treatment for fractures is of ongoing interest and becoming more relevant with an aging population and finite health resources. Trochanteric fractures constitute approximately half of all hip fractures with the medial calcar critical to fracture stability. In the management of unstable trochanteric fractures, it is assumed that intramedullary nails and longer implants will lead to less failure. However, the lack of power, inclusion of older generation femoral nails, and a variable definition of stability complicate interpretation of the literature. Materials and Methods: Between January 2012 and December 2017, a retrospective analysis of operatively treated geriatric trochanteric hip fracture patients were examined at a Level 1 Trauma Centre. The treatment was with a long and short version of one type of trochanteric nail. Unstable trochanteric fractures with medial calcar comminution were examined (AO31A2.3, 2.3 & 3.3). The length of the medial calcar loss, nail length, demographics, fracture morphology, and relevant technical factors were examined in univariate and multivariate analysis using competing risk regression analysis. The primary outcome was failure of fixation with post-operative death the competing event and powered to previously reported failure rates. Results: Unstable patterns with medial calcar comminution loss constituted 617 (56%) of operatively treated trochanteric fractures. Failure occurred in 16 (2.6%) at a median post-operative time of 111 days (40–413). In univariate and multivariate analysis, only younger age was a significant predictor of failure (years; SHR: 0.91, CI 95%: 0.86–0.96, p < 0.001). Nail length, medial calcar loss, varus reduction, and other technical factors did not influence nail failure. Conclusions: In a cohort of unstable geriatric trochanteric hip fractures with medial calcar insufficiency, only younger patient age was predictive of nail failure. Neither the length of the medial calcar fragment or nail was predictive of failure.